Kerja Sama Guru PAI dan Shadow Teacher dalam Meningkatkan Hasil Belajar Siswa Autisme di SMP IT Nurul Ilmi Medan - Reni Pratiwi; Afrahul Fadhila Daulai; Enny Nazrah Pulungan (Jurnal Cakrawala Akademika, 2024)
Abstract. This research is based on one of the schools in Medan which has children with special needs autism who are assisted by Shadow Teachers in the learning process, namely at Nurul Ilmi IT Middle School. The focus of this research is also on PAI teachers who also help in the PAI learning process. So there is a need for cooperation between PAI teacher with Shadow Teacher in helping the learning process of the child with Autism. This research uses a qualitative research method using a case study approach. Data collection techniques using observation, interviews and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions The results of the research show that the PAI Teacher collaborates with the Shadow Teacher, namely the PAI Teacher explains the material in front of the class and then the Shadow Teacher delivers the material to students with Special Needs individually using private media selection. The obstacles encountered by both of them were reluctance to communicate with each other due to hesitation, lack of communication and time. The efforts that can be made by both of them are staying focused on their respective tasks, improving communication, aligning views, and taking the time to improve cooperation between the two of them in between times.